Media Literacy: The Effect of News on Covid-19 in Mass Media in Public Understanding - Eryza Eryza; Rafinita Aditia (Politeknik Negeri Media Kreatif, 2023)
The news that is currently being hotly reported by the media is Covid-19. This news should be able to be literate by the public. Media literacy is a concept about the ways in which people question what they hear, read, and watch from the media. So that people are able to control media content critically and intelligently and are able to read propaganda, bias, or certain interests from a media report. News about COVID-19 has been widely published by the media in Indonesia. One of the reports is from CNN Indonesia which discusses the Covid-19 death rate which is small but more deadly than the flu. The RRI (Radio Republik Indonesia) website also reflects reports about the Covid-19 virus, which is ten times more deadly than swine flu. The continuous flow of news provides various meanings of media literacy for each community. Some people are still not literate in the media and accept all news raw, without any further study and study of the Covid-19 news presented by the media. As a result, the decadence of humanity has become an unavoidable phenomenon. This humanitarian decadence occurs through panic buying and rejection of Covid-19 positive bodies.